Effects of neferine on heart electromechanical activity in anaesthetized cats - LI Gui-rong; QIAN Jia-qing; LV Fu-hua (Acta Pharmacologica Sinica, 2016)
Neferine, an alkaloid extracted from the green seed embryo of Nelumbo nucifera Gaertn, has been shown to have anti-arrhythmic action. Neferine 1-10 mg/kg iv dose-dependently decreased the monophasic action potential amplitude (MAPA), prolonged the monophasic action potential duration (MAPD). It also decreased LVP, dP/dt, prolonged SCL, and reduced arterial blood pressure in a dose-dependent manner. These effects were similar to those of quinidine, and different from tetrandrine. The latter had an inhibitory effect on LVP and dP/dt, but had no influence on MAPA and MAPD. The results indicate that neferine and quinidine have similar effects on heart electro-mechanical activity.